1998
DOI: 10.1074/jbc.273.41.26946
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Sequence Requirement for Efficient Incorporation of Glycosylphosphatidylinositol-associated Proteins into the Cell Wall of Saccharomyces cerevisiae

Abstract: During cell wall biogenesis in Saccharomyces cerevisiae, some glycosylphosphatidylinositol (GPI)-attached proteins are detached from GPI moieties and bound to ␤-1,6-glucan of the cell wall. The amino acid sequence requirement for the incorporation of GPI-attached proteins into the cell wall was studied by using reporter fusion proteins. Only the short -minus region composed of five amino acids, which is located upstream of the site for GPI attachment, determined the cellular localization of the GPI-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 50 publications
6
77
0
Order By: Relevance
“…In order to predict which GPI proteins remain attached to the plasma membrane and which proteins are covalently attached to β-1,6-glucan in the cell wall, we have analysed the sequence requirements for the ω − region for efficient incorporation of proteins into the cell wall, as proposed by earlier studies on S. cerevisiae (Hamada et al, 1998b, Identification of fungal GPI proteins 795 1999; Vossen et al, 1997). First, we have analysed in known S. cerevisiae cell wall proteins the occurrence of V, I or L at positions 4 or 5 amino acids upstream of the ω site and of Y or N two amino acids upstream of the predicted ω sites, which has been shown to be positively correlated with cell wall incorporation (Hamada et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to predict which GPI proteins remain attached to the plasma membrane and which proteins are covalently attached to β-1,6-glucan in the cell wall, we have analysed the sequence requirements for the ω − region for efficient incorporation of proteins into the cell wall, as proposed by earlier studies on S. cerevisiae (Hamada et al, 1998b, Identification of fungal GPI proteins 795 1999; Vossen et al, 1997). First, we have analysed in known S. cerevisiae cell wall proteins the occurrence of V, I or L at positions 4 or 5 amino acids upstream of the ω site and of Y or N two amino acids upstream of the predicted ω sites, which has been shown to be positively correlated with cell wall incorporation (Hamada et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of basic residues in the region immediately upstream of the GPI attachment site (ω − region) is favoured in proteins that are predominantly localized in the plasma membrane . On the other hand, the presence of V, I or L at 4 or 5 amino acids upstream of the ω site (ω-4, ω-5) and Y or N at ω-2 has been shown to act as a positive signal for cell wall localization (Hamada et al, 1998b(Hamada et al, , 1999. Thus, GPI protein localization seems at least partly to be determined by the amino acids in the ω − region.…”
Section: Introductionmentioning
confidence: 99%
“…If this region includes two basic amino acids, the protein will be mostly retained in the plasma membrane (Caro et al 1997;Frieman and Cormack 2003), but if basic residues are absent or replaced with hydrophobic ones, the predominant location is the wall (Hamada et al 1998b(Hamada et al , 1999Frieman and Cormack 2003). However, having two basic amino acids in the v(2) region does not guarantee membrane localization because the additional presence of a longer stretch of amino acids rich in Ser and Thr will override the dibasic motif and shift the protein to the wall (Frieman and Cormack 2004).…”
Section: Incorporation Of Gpi Proteins Into the Wallmentioning
confidence: 99%
“…This skeletal layer is strengthened by coupling of chitin chains to non-reducing ends of b1,3-glucan chains. At the outside of this layer, two types of cell wall proteins (CWPs) have been identified that are covalently linked to b-glucan, namely the proteins with internal repeats (Pir)-CWPs, which are linked to the b-1,3-glucan network via an alkaline-sensitive linkage, and the glycosylphosphotidylinositol (GPI)-CWPs, which are linked to the b1,3-glucan network via short chains of b1,6-glucan (Kapteyn et al, 1997Mrsa et al 1997;Hamada et al, 1998). Collectively, these CWPs limit the cell wall permeability, although some of them are involved in specific cellular functions, including flocculation, pseudohyphal growth and sexual agglutination (Cid et al, 1995).…”
Section: Introductionmentioning
confidence: 99%